Preliminary study: The effect of gibberellic acid and girdling application on two dual-purpose grape varieties in a cool climate - Tóth, Adrienn Mária; Zsófi, Zsolt; Veres, Szilvia (Acta Agraria Debreceniensis, 2025)
In our 2023 experiment, Nero and Muscat Pölöskei grapevines were treated with gibberellic acid (12 mg L-1) during flowering, followed by stem-end girdling at the onset of berry development. Photosynthetic activity was monitored regularly. Assimilation rate (A, µmol CO₂ m⁻² s⁻¹) and transpiration rate (E, mol H₂O m⁻² s⁻¹) were measured under natural light. Sugar content and acidity were assessed via refractometry, while berry dimensions and texture (e.g., berry hardness [Bh, mN]) were recorded. Gibberellin treatment increased sugar content compared to both control and girdled samples. However, girdling significantly enhanced sugar accumulation in Muscat Pölöskei compared to untreated samples. Gibberellin also induced berry elongation, increasing the longitudinal axis in Nero (19%) and Muscat Pölöskei (24%). Girdling temporarily reduced photosynthetic activity, which recovered post-healing. The elongated berries due to gibberellin treatment led to a looser cluster structure, which is beneficial for Nero, which is prone to fungal diseases due to dense clusters.